The Concept of a Natural Object As an Element of the Forensic Databases - O. B. Dronova; I. V. Ryzhkov (Теория и практика судебной экспертизы, 2021)
A natural object as an element of the system of accounting and registration activities has a dual nature, which determines the multidirectional functional purposes of its use. On the one hand, as an object of reference funds, it conveys a system of properties and attributes inherent in it as in an independent material object. On the other hand, a natural object acts as one of the forms of keeping forensic records, containing important information about a trace-forming object and the mechanism of trace formation. The currently existing theoretical approaches to the deﬁnition of a “natural object” do not fully consider its speciﬁcity and the variety of its constituent elements.The article addresses the etymological, subject, and functional approaches to the essence of a natural object, determining its position and status in the system of forensic databases. The analysed features determine the possibility of using this form of information storage as an object of identiﬁcation, diagnostic and situational expert research. The authors propose a “natural object” deﬁnition as a material source of primary (primary-reﬂected) objective information, containing a set of properties and features resistant to time factors that form derived information. The suggested deﬁnition provides a precise understanding of the considered analysed of a “natural object” for further use in departmental regulatory documents and scientiﬁc and practical works.